Optimization of Platelet-Rich Plasma Fraction Selection for Surgical Treatment of Macular Holes - V. N. Kazaykin; N. S. Demchenko; A. Yu. Kleimenov (Oftalʹmologiâ, 2023)
Objective: based on clinical and morpho — functional analysis of retinal restoration and assessment of the cellular composition of platelet-rich plasma, to determine its optimal fraction for surgical treatment of macular hole. Materials and methods. This study presents the results of 120 cases of surgical treatment of eyes with macular hole. The patients were divided into 2 groups. In the 1st group (60 eyes), the technology developed in our clinic was used without the use of postoperative tamponade of the vitreal cavity and the use of autologous platelet-rich plasma (PRP), in the 2nd — traditional technology for the treatment of macular hole s (60 eyes). The cellular composition of the PRP of 30 patients was analyzed. Results. 2 months after surgery, 119 patients had the restoration of all retinal layers in the macular hole area and positive dynamics of visual acuity was recorded in comparion with the preoperative period. After observation for 6 months after surgery, cases of recurrence of macular hole were not detected. Conclusion. The therapeutic value of BoTP lies in the tamponing and regenerative effect. According to the results of this study, for maculrupture surgery, it is rational to use plasma from a layer of pure platelet-rich plasma (P-PRP), which contains a sufficient number of platelets capable of having a positive therapeutic effect, and a minimum number of leukocytes capable of performing the functions of immune protion and repair of the retiand surrounding tissues.